2022
DOI: 10.3390/molecules27030589
|View full text |Cite
|
Sign up to set email alerts
|

Portable vs. Benchtop NIR-Sensor Technology for Classification and Quality Evaluation of Black Truffle

Abstract: Truffles represent the best known and most expensive edible mushroom. Known as Ascomycetes, they belong to the genus Tuber and live in symbiosis with plant host roots. Due to their extraordinary taste and smell, truffles are sold worldwide for high prices of up to 3000–5000 euros per kilogram (Tuber magnatum PICO). Amongst black truffles, the species Tuber melanosporum VITTAD. is highly regarded for its organoleptic properties. Nonetheless, numerous different sorts of black truffle are offered at lower prices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…Previous results have shown that microPHAZIR showed a similar or even better discrimination capability than benchtop devices ( Zamora-Rojas et al, 2012 ), which coincides with the results obtained. On the other hand, these results differ from those previously reported by Kappacher et al (2022) who found that better discrimination results from intact samples were obtained with NIRFlex N-500 and MicroNIR 1700. Other studies also indicated that MicroNIR 1700 showed a similar discrimination ability to benchtop devices ( de Lima et al, 2018 ; Liu et al, 2018 ), which does not agree with the results of this study in which the worst results were obtained with this device.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous results have shown that microPHAZIR showed a similar or even better discrimination capability than benchtop devices ( Zamora-Rojas et al, 2012 ), which coincides with the results obtained. On the other hand, these results differ from those previously reported by Kappacher et al (2022) who found that better discrimination results from intact samples were obtained with NIRFlex N-500 and MicroNIR 1700. Other studies also indicated that MicroNIR 1700 showed a similar discrimination ability to benchtop devices ( de Lima et al, 2018 ; Liu et al, 2018 ), which does not agree with the results of this study in which the worst results were obtained with this device.…”
Section: Resultscontrasting
confidence: 99%
“…The Hadamard-transform principle, the Fabry–Perot filter, the micro-optoelectro-mechanical system (MOEMS), and the linear variable filter (LVF) coupled with an array detector or dispersive grating combined with a digital micro-mirror device (DMD) can be mentioned for the optical configurations employing single-element detectors, which lead to different operational wavelength regions, spectral resolution, and signal to-noise ratios ( Beć et al, 2021a , 2021b ). These drawbacks may affect the analytical performance or the applicability to a specific matrix ( Plans et al, 2013 ; Pu et al, 2021 ; Sun et al, 2020 ; Yu et al, 2020 , 2020b; Kappacher et al, 2022 ). In fact, although portable NIR spectroscopy has great potential in the meat sector ( Kademi et al, 2019 ) and this equipment has been used on pork meat and carcasses in order to classify ( Zamora-Rojas et al, 2012 , 2013 ; Horcada et al, 2020 ; Pérez-Marín et al, 2022 ) and predict certain quality parameters such as the basic composition, color, texture, fatty acids, the iodine value, thiobarbituric reactive substances (TBARS), or stable isotopes ( Garrido-Varo et al, 2016 ; Prieto et al, 2018 ; Piotrowski et al, 2019 ; Kucha and Ngadi, 2020 ; González-Martín et al, 2021 ), only a few portable equipment devices have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of these approaches are quite time-consuming or require special laboratory infrastructure. The only exception is the recording of near infrared (NIR) spectra, 19,20 which, though, cannot unambiguously identify potential marker compounds that can be used to develop a rapid test.…”
Section: Introductionmentioning
confidence: 99%
“…Near‐infrared spectroscopy is used for the taxonomic identification of mushrooms and detection of adulteration is also very effective. Kappacher et al 149 . showed that the NIR technique can identify different black truffle species with up to 100% accuracy.…”
Section: New Detection Technologiesmentioning
confidence: 99%